Biomaterial–Related Cell Microenvironment in Tissue Engineering and Regenerative Medicine. (June 2022) - Gao, Jingming; Yu, Xiaoye; Wang, Xinlei; He, Yingning; Ding, Jiandong
Abstract: An appropriate cell microenvironment is key to tissue engineering and regenerative medicine. Revealing the factors that influence the cell microenvironment is a fundamental research topic in the fields of cell biology, biomaterials, tissue engineering, and regenerative medicine. The cell microenvironment consists of not only its surrounding cells and soluble factors, but also its extracellular matrix (ECM) or nearby external biomaterials in tissue engineering and regeneration. This review focuses on six aspects of biomaterial–related cell microenvironments: ① chemical composition of materials, ② material dimensions and architecture, ③ material–controlled cell geometry, ④ effects of material charges on cells, ⑤ matrix stiffness and biomechanical microenvironment, and ⑥ surface modification of materials. The present challenges in tissue engineering are also mentioned, and eight perspectives are predicted.